Determinants of Bank Liquidity in the Middle East Region - El-Chaarani, Hani (International Review of Management and Marketing, 2019)
The objective of this study is to examine the determinants of bank liquidity in the Middle East region. It also aims to compare the liquidity levels of banking sectors between Middle Eastern countries. Two different liquidity measures, four bank specific factors and three macroeconomic factors have been manipulated by using the WLS regression on 183 banks from eight different countries during a period of three years (2014, 2015 and 2016).The research employed “loans-to-assets” and “loans-to-deposits” as proxies to measure the bank's liquidity level. The bank specific factors include assets quality, performance level, capitalization ratio and bank size. The macro economic factors used in this study are economic growth, unemployment and inflation rates. The results indicate that Lebanese banks have the highest level of liquidity whereas Omani banks have the lowest level of liquidity. In addition, the study shows a decreasing of bank liquidity during 2016 in Middle Eastern countries. The additional analysis reveals the significant impacts of economic growth, assets quality, capital level and bank size on liquidity in the banking sector. Finally, the results reveal that larger banks have to monitor their liquidity risks by controlling the level of provided loans and, they recommend central banks keep an eye on equity ratio and non-performing percentage of loans especially during economic growth. Keywords: Liquidity, banks, capital structure, performance, economic growth, unemployment, inflation. JEL Classifications: G21, J6 DOI: https://doi.org/10.32479/irmm.7742